Executive search and selection: Imperfect theory or intractable industry? - BRITTON, L. C. (Institutional Knowledge at Singapore Management University, 1992)
This paper is a structure conduct performance analysis of the executive search and selection industry. The industry illustrates well the general problems of applying this framework to service industries. Structure and conduct can be analysed with some modifications to techniques but it is in the area of performance that the analysis is most difficult to apply. Much of the analysis is based on a comprehensive survey of the UK industry carried out by the authors.